Changes over time in muscle fatty acid composition of Malaysian mahseer, Tor tambroides, fed different dietary lipid percentage - Fard, Ehsan Ramezani; Kamarudin, Mohd Salleh; Saad, Che Roos; Harmin, Sharr Azni (Academic Journals, 2011)
The effects of four isonitrogenous diets containing different lipid levels on the muscle fatty acid profiles of Malaysian mahseer were evaluated over a period of six weeks from June to July, 2010. A general increase of monounsaturated fatty acid contents in the muscle of fish that were fed the test diets was detected after two weeks. Despite the high total content of long chain n-3 polyunsaturated fatty acid (PUFA) in the formulated diets, the levels of these fatty acids in the muscle did not increase and it may be speculated that the content of long chain n-3 PUFAs in this species was determined by desaturation and elongation of shorter chain fatty acids rather than direct absorption from the diet. Moreover, reduction of muscle n-3 PUFA content after six weeks of feeding showed that a diet containing high level of n-3 PUFA may not be able to provide all the essential fatty acid requirements of T. tambroides.